Frameworks Without Ground: A Critical Review of Sustainability Concept Development and Its Limits for Alternative Economic Thought (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Sustainable development discourse has operated for over three decades under an unresolved foundational tension: the Brundtland Commission's canonical 1987 definition accommodated continued economic growth as a political condition of international consensus, while the ecological systems that definition was designed to protect have continued to deteriorate. By 2023, six of nine quantified planetary boundaries had been transgressed. This paper conducts a thematic review of seventeen papers spanning the bibliometric, normative-ecological, and political-economic traditions within sustainability research, identifying four structural problems that the field has not resolved: the causal gap between knowledge production and measurable outcomes; the paradigm-replacement problem concerning neoclassical economics; the foundational dependency of the entire literature on Planetary Boundaries evidence it does not independently validate; and the Global South absence problem. The review finds that alternative economic frameworks — Doughnut Economics, post-growth theory, ecological economics, and capabilities-based approaches — have reached theoretical maturity and demonstrated governance operationalizability, but have been developed exclusively in and for high-income, post-industrial economies. The paper argues that the Global South is not a representational gap to be corrected by inclusive citation practice, but the site where existing frameworks' deepest assumptions about the relationship between economic growth, human development, and ecological constraint are most consequentially tested. It proposes a theoretical reconstruction of post-growth and doughnut economics frameworks that engages the specific political economy of Southern developmental contexts — marked by unmet social foundations, constrained fiscal and institutional capacity, colonial resource extraction histories, and asymmetric international financial architecture — as the condition for producing a genuinely global alternative economics of sustainability.